Pembahasan Injil Harian dalam Komunitas Virtual Awam - Tiro Angelo Daenuwy; Indra Tanureja (Media: Jurnal Filsafat dan Teologi, 2023)
This study seeks to provide an initial understanding of how lay Catholics in Indonesia engage with and interpret the texts of the Holy Scripture within virtual spaces. Specifically, it examines the WhatsApp group GEMA Kotabaru using netnography as a research method to explore the group's interpretation of the Gospel passage Luke 17:1-6. The findings reveal two distinct patterns of interpretation: symbolic and literal. Symbolic interpretation involves members connecting the text to metaphors of faith and religious practices, while literal interpretation focuses on extracting the precise meaning of the text, including the significance of the mustard seed. These findings highlight that lay Catholics in the WhatsApp group tend to center their Scripture readings around religious practices and strive to comprehend the text in a manner that resonates with their daily lives.